Design of a Solar Powered Battery Charger - Adlina, Anis; Embong, Zaidi; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2023)
Renewable energy sources include biomass power, wind power, hydroelectricity and most widely used is solar energy. Solar energy may be captured by utilising a solar panels, which directly turns sunlight into electrical energy. Many tiny electrical equipment, such as battery chargers, can also benefit from solar electricity. A solar-powered battery charger for a motorised wheelchair is constructed in this project to charge lead acid batteries and signal the user when the batteries are fully charged. One of the least expensive ways to charge batteries is the main benefit of using a solar-powered battery charger. In addition, solar powered battery chargers are quickly gaining acceptance since they have been shown to be useful in a variety of settings, particularly in the outdoors, as well as being user friendly and portable. A constant current source is employed to replenish the batteries in this project, and the capacitance of the lead acid battery is successfully measured. When the batteries have been fully charged, an LED light bulb will activate to notify the user that the batteries may now be utilised.